Integrated Evaluation of Sustainability and Quality of Italian Tomato Cultivars Grown Under Irrigated and Non-Irrigated Systems - Giuliana Vinci; Paola Campana; Laura Gobbi; Sabrina Antonia Prencipe; Marco Ruggeri (Agriculture)
This research aimed to assess how irrigation can affect the sustainability and quality of two Italian tomato cultivars: the “Riccio di Parma Casertano,” which is grown without irrigation, and the “Piennolo del Vesuvio DOP,” which requires irrigation. Life cycle assessment and water footprint analysis were used for sustainability assessment, while, for quality assessment, the content of bioactive compounds was analyzed by UV-Vis spectrophotometric assays. The results indicate that ‘Riccio di Parma Casertano’ is a more sustainable cultivar than ‘Piennolo del Vesuvio DOP’, with lower environmental impacts in all 18 impact categories, showing reductions ranging from 54.55% to 99.90%. This higher sustainability performance of “Riccio di Parma Casertano” is also characterized by increases of +32% in total polyphenol content and +43% in total flavonoid content as an adaptive response to water stress compared with “Piennolo del Vesuvio DOP”. However, “Piennolo del Vesuvio DOP” has a higher yield and better overall nutritional and functional quality, with higher concentrations of hydrophilic and lipophilic compounds, such as lycopene and β-carotene, due to irrigation. The results, therefore, show how the choice between the two cultivars might depend on a trade-off between sustainability and quality. In particular, ’Riccio di Parma Casertano’ could excel in contexts with low water availability while maintaining a good nutritional profile due to the synthesis of bioactive compounds; on the other hand, “Piennolo del Vesuvio DOP” could offer higher yield and nutritional qualities, although it needs improved agricultural practices to reduce overall environmental impacts.